Examples of Open Data Use in Slovenia - Marolt, Marjeta; Vidmar, Doroteja; Lenart, Gregor (Odprti podatki kot pospeševalec družbenih, okoljskih in gospodarskih inovacij – priložnosti in izzivi, 2026)
The chapter summarises the development of open data in the international and Slovenian context, focusing on its role in promoting transparency, innovation and improving public services. In Slovenia, open data is increasingly gaining traction through the national OPSI portal and funding programmes that promote its development. This has led to the emergence of several good practice examples, including the Environmental Atlas, Mobility Map, Doctors Tracker, Promet.si, Parlameter, Autolog, Statist, eVineyard and Tourism Daily. These use cases illustrate the use of open data in different areas such as mobility, health, environment, agriculture, tourism, real estate and energy. However, Slovenia faces challenges such as inconsistent data quality, lack of standards and low uptake in the economy. Improved digital infrastructure, legal coherence and user awareness are necessary to make more effective use of open data. Using suitable approach, Slovenia can achieve a higher level of digital transformation and enhance the competitiveness of its economy on a global scale.